Delirious Mania Associated with Autoimmune Gastrothyroidal Syndrome of a Mid-Life Female: The Role of Hashimoto Encephalopathy and a 3-Year Follow-Up including Serum Autoantibody Levels - Udo Bonnet; Claudia Selle; Ralf Kuhlmann (Case Reports in Psychiatry)
We report the case study of a 57-year-old Caucasian female with steroid-responsive encephalopathy associated with autoimmune thyroiditis (SREAT), commonly termed Hashimoto encephalopathy (HE). This presentation includes one of the longest lasting follow-up studies of HE considering the neuropsychiatric symptoms (here delirium, mania, and EEG-slowing) and their relation to serum autoantibody levels. Antithyroid-peroxidase autoantibodies, the hallmark of autoimmune thyroiditis, were found in the serum and also in the cerebrospinal fluid. Diagnostic analyses found no evidence of limbic encephalopathies characterized by serum antibodies against intracellular, synaptic, or further cell surface antigenic targets, neoplasm, and connective tissue or vasculitis diseases. A potential contribution of bipolar disorder and metabolic encephalopathies due to severe hypothyroidism, glucocorticoid treatment, accelerated thyroid hormone replacement therapy, or vitamin B deficiency is critically discussed. Another special feature of this case report is the linkage of HE to an autoimmune polyendocrine syndrome (type 3B) affecting the gastroduodenum in addition to the thyroid gland.